Matrix morphology and the particle dispersion in HDPE nanocomposites with enhanced wear resistance. (August 2019) - Pelto, Jani; Verho, Tuukka; Ronkainen, Helena; Kaunisto, Kimmo; Metsäjoki, Jarkko; Seitsonen, Jani; Karttunen, Mikko
Abstract: High density polyethylene nanocomposites were prepared by melt mixing of varying type of nanopowders in the presence of vinyltrimethoxysilane (VTMS) coupling agent. Three spherical/irregular-shaped nanopowders, fumed Al2 O3, γ-Al2 O3, cubic titanium nitride (TiN) (1.5 vol-%), and high aspect ratio graphene oxide platelets (GO) (0.5 vol-%) were investigated in a high molecular weight HDPE matrix. Significant differences in the dispersion quality between the nanopowders were found by TEM and AFM. Degree of crystallinity of the nanocomposites (DSC/XRD) was consistently lower than in the neat HDPE polymer. The particularly well dispersed fumed Al2 O3, γ-Al2 O3 and GO nanopowders induced significant modification on the micromechanical properties of the HDPE. For the first time, great enhancement in the sliding wear performance, and an improvement in the abrasive wear performance was found in the high molecular weight HDPE nanocomposites. DSC analyses showed elevations in the glass transition temperatures and the peak melting temperatures of the nanocomposites. XRD peak splitting in the HDPE + GO and the HDPE + γ-Al2 O3 nanocomposites suggest the emergence of a concurrent orthorhombic HDPE phase. Formation of new phases was also supported by DSC analyses showing broad and multimodal melting peaks. Scherrer analyses of XRD data showed slightly increased HDPE crystalline thicknesses in the range of 15–20 nm in the nanocomposites, which was in line with the TEM and AFM observations. The great elevation in the melting temperatures of the HDPE nanocomposites with fumed Al2 O3 and γ-Al2 O3 could not be attributed to the polymer lamellar thickness, but rather to the altered properties of the solid amorphous phase stemming for the nanopowder additives. Highlights: Crystallinity of HDPE reduced by fumed aluminium oxide, g-aluminium oxide, titanium nitride and graphene oxide (GO). Micromechanical properties of the HDPE polymer significantly changed by the finely dispersed fumed Al2 O3, g-Al2 O3 and GO. Enhanced sliding wear and sand abrasion test performance observed for the g- and the fumed aluminium oxide nanocomposites. Significant elevations in the glass transition of HDPE found in the nanocomposites. Greatly elevated melting temperatures observed in the fumed Al2 O3, g-Al2 O3 and GO nanocomposites.